Power / Truth, Resistance / Subjugation: The Discursive Theater of the Avengers (Global Journal of Human-Social Science, 2021)
This article comes from studies carried out during the post-doctoral internship, between March and December 2019, at the Federal University of Pernambuco. During this period, The Avengers' filmography was observed, taking as theoretical basis Foucault's researches, Archaeology and Genealogy. In this work, four enunciative sequences taken from the film "The Avengers" (2012), a Marvel Cinematographic Universe component, are presented and analyzed. In this Universe, the stories form a network of overlapping narratives, a discourse field (FOUCAULT, [1969] 1997), from which multiple contrasts are perceived: utopia/dystopia; violence/peace; subjugation/ resistance, promoting truth effects. As an analysis instrument, three questions were elaborated, trying to establish the relationship between the Foucauldian concepts and the research object. They are: which truth effects are produced from this film circulation? How are the heroes and villains' images produced in this filmic materiality? What is the relationship between film media and the 'history of the present'? In response to these questions, it was found that this filmography is crossed by political, mythical, religious, scientific discourses (with the emphasis on the power of weapons technology).
Keywords: avengers; archaeology; genealogy; discourse